Bone loss at the distal femur and proximal tibia in persons with spinal cord injury: imaging approaches, risk of fracture, and potential treatment options. Issue 3 (March 2017) - Cirnigliaro, C.; Myslinski, M.; La Fountaine, M.; Kirshblum, S.; Forrest, G.; Bauman, W.
Abstract Persons with spinal cord injury (SCI) undergo immediate unloading of the skeleton and, as a result, have severe bone loss below the level of lesion associated with increased risk of long-bone fractures. The pattern of bone loss in individuals with SCI differs from other forms of secondary osteoporosis because the skeleton above the level of lesion remains unaffected, while marked bone loss occurs in the regions of neurological impairment. Striking demineralization of the trabecular epiphyses of the distal femur (supracondylar) and proximal tibia occurs, with the knee region being highly vulnerable to fracture because many accidents occur while sitting in a wheelchair, making the knee region the first point of contact to any applied force. To quantify bone mineral density (BMD) at the knee, dual energy x-ray absorptiometry (DXA) and/or computed tomography (CT) bone densitometry are routinely employed in the clinical and research settings. A detailed review of imaging methods to acquire and quantify BMD at the distal femur and proximal tibia has not been performed to date but, if available, would serve as a reference for clinicians and researchers. This article will discuss the risk of fracture at the knee in persons with SCI, imaging methods to acquire and quantify BMD at the distal femur and proximal tibia, and treatment options available for prophylaxis against or reversal of osteoporosis in individuals with SCI.